Prenatal Diagnosis of Otocephaly by Three-dimensional Ultrasonography - Fang-Yu Hung; Kuo-Gon Wang; Chih-Ping Chen; Chin-Yuan Hsu (Elsevier, 2004)
Objective: Otocephaly is a rare congenital malformation complex. The purpose of this paper is to report our experience of prenatal diagnosis using three-dimensional ultrasonography. Case Report: A 30-year-old primigravida was referred at 29 weeks of gestation for polyhydramnios and regular uterine contractions. Two-dimensional ultrasound revealed a live fetus with biometric data appropriate for 29 weeks of gestation, polyhydramnios, absence of the mandible, hypotelorism, low-set ears, and left microphthalmia with right anophthalmia. Three-dimensional ultrasound demonstrated the facial anomalies of otocephaly, including agnathia, microstomia, and low-set ears conjoining the median line. Conclusion: A combination of two- and three-dimensional ultrasound is useful in the prenatal diagnosis of otocephaly for the whole view of the facial malformation.